THE INDONESIAN NATIONAL ARMED FORCES (TNI) AND FALINTIL- FORÇAS DE DEFESA DE TIMOR LESTE (F-FDTL)’S DEFENSE DIPLOMACY: A WAY OF CONFLICT RESOLUTION IN TIMOR LESTE - Khory Wandira Ambarsari; Helda Risman (The Republic of Indonesia Defense University, 2019)
Indonesia and Timor Leste have had an irrelevant relationship related to the history of Seroja Operation on 7 December 1975 when the TNI, formerly known as ABRI (Armed Forces of the Republic of Indonesia) carried out a total military operation in order to keep Timor Leste for not separate from Indonesia, while later it caused losses where many TNI and Falintil- Forças De Defesa De Timor Leste (F-FDTL)’s personnel were killed in the war. Time passed, now the relationship between both countries is getting better due to the efforts from the Indonesian and Timor Leste’s parties, especially the national armies, had been done. To solve the conflict between those countries, defense diplomacy is needed. In this article, the writers tend to describe how both armed forces conduct defense diplomacy so Indonesia and Timor Leste’s relationship is getting better, indeed now both countries have done some collaborations in some aspects in the economy and military. Later, the writers will analyze more to find out the best conflict resolution that had been done by both armed forces, and the existence of each State Leaders’ participation. It is clearly stated that by utilizing defense diplomacy through visiting state leaders, having an official meeting, holding military cooperation such as doing exchange troops are some best ways of conflict resolution that can be done by Indonesia and Timor Leste to create a better relationship.Keywords: Defense Diplomacy, Conflict Resolution, Indonesia National Army (TNI), F-FDTL, Timor Leste